Educating Innovators of Future Internet of Things - Osipov, Evgeny; Riliskis, Laurynas (2013 IEEE Frontiers in Education Conference (FIE), 2013)
Clouds, Communicating Machines, Social Networking, Big Data, innovative web-services are the buzz words that currently ramp up the interest in computer science education amongst potential students. The current trend in CS education is to introduce an innovation component into the content of undergraduate and graduate courses facilitating out of the box thinking. In the fall of 2012 the content of three undergraduate courses running in parallel at Luleå University of Technology were aligned in the theoretical and practical parts projecting the individual contents to a holistic scenario of the Internet of Things. The practical goal of the trial was to provide skills of developing innovative, cutting-edge IT solutions. The trial courses were: Wireless sensor networks, Distributed applications, and Network programming. The first two courses are given on the fourth year while the later course is given on the second year of the CS program. The theoretical content of three courses allowed creating a scenario covering the whole technology chain of the Internet of Things: gathering and communicating sensory data; scalable and distributed processing of big data; value-added, human relevant network services. In the practical part students in the three courses (total 60) acted as start-up companies in the respective technology domain. These ``start-ups'' were assigned a task to deliver a common holistic system given time, performance and budget constrains. This task required students in a particular course to constantly communicate to other students outside the course's boundaries. Through these activities students were trained on skills for industrial level development and integration of complex IT systems. On a technical side all courses were conducted using Amazon Web Services as a common computing platform. This choice allowed us to draw interesting conclusions about students work load, the degree of their actual involvement in the learning process as well as economical costs. In the sensor network course a ...